Navigating preemptive and therapeutic donor lymphocyte infusions in advanced myeloid malignancies by high-sensitivity chimerism analysis - Stadler, Michael; Venturini, Letizia; Bünting, Ivonne; Dammann, Elke; Weissinger, Eva M.; Schwarzer, Adrian; Schultze-Florey, Christian; Ehrlich, Steve; Markel, Dominik; Lueck, Catherina; Gladysz, Alexandra; Fröhlich, Tabea; et al. (Frontiers in Oncology, 2022)
Preemptive and therapeutic donor lymphocyte infusions (preDLI and tDLI) are widely used in relapsing and relapsed hematopoietic malignancies after allogeneic stem cell transplantation (alloSCT) to enhance the graft-versus-malignancy effect. However, in advanced myeloid malignancies, long-term survival after preDLI and tDLI remains low, reflecting our inability to master the double-edged sword of alloreactivity, balancing anti-neoplastic activity versus graft-versus-host disease (GvHD). We previously evaluated a quantitative PCR-based high-sensitivity chimerism (hs-chimerism) based on insertion/deletion polymorphisms instead of short tandem repeats, where increasing host chimerism in peripheral blood predicts relapse more than a month before clinical diagnosis, and declining host chimerism signals anti-host alloreactivity. Here we report 32 consecutive patients with advanced myeloid malignancies receiving preDLI or tDLI “navigated” by hs-chimerism (“navigated DLI”). We compared them to a historical cohort of 110 consecutive preDLI or tDLI recipients, prior to implementation of hs-chimerism at our institution (“controls”). Both groups were comparable regarding age, gender, conditioning, donor type, and time to DLI. With longer median follow-up of the navigated DLI group (8.5 versus 5 months), their landmark overall (64%) and disease-free survival (62%) at 2 years from first DLI compared favorably with controls (23% and 21%, respectively). Improved survival of navigated DLI was due to both reduced relapse incidence (38% versus 60%) and non-relapse mortality (17% versus 44%) at 2 years. Early relapse prediction by hs-chimerism allowed a preemptive approach in 28% of navigated DLI versus 7% in controls. Our results confirm hs-chimerism as a highly valuable tool for monitoring and steering immune interventions after alloSCT.